Alone - Virta, Nikaloi; Gullick, J. M. (Kuala Lumpur : New York : Oxford University Press, 1995)
"Exotic cultures, strange lands, and proud monarchies confronted the Portuguese and Spaniards who came to South-East Asia in the sixteenth century with the practical objectives of securing control of the profitable trade in export of spices to Europe, and - to a lesser extent - of combating Islam, their traditional foe in the Mediterranean. The pursuit of commercial and strategic advantages brought the Dutch, English, and French on their heels. Later still, the nineteenth century saw the arrival of explorers seeking to discover the sources of the great rivers of the region, naturalists who ranged far afield to collect specimens, and literary travellers, professional photographers, married women, and other visitors who recorded their experiences." "This anthology offers selections from the abundant range of European writing, expressing the fascination, the excitement, and sometimes the violence or danger of personal adventures and encounters in South-East Asia. It is the work of a talented minority who found delight in a strange world of their time, a world which is rapidly changing and vanishing. These writers have left a vivid record for the entertainment of the modern reader."--BOOK JACKET.
34.Yusuf Reunited with his Mother in Central Java/Arthur Keyser.
Includes bibliographical references.
Keywords: Europeans -- Southeast Asia; Southeast Asia -- Description and travel